2018
DOI: 10.1002/slct.201801578
|View full text |Cite
|
Sign up to set email alerts
|

A Study On Synthesis, Biological Activities and Molecular Modelling of Some Novel Trisubstituted 1,2,4‐Triazole Derivatives

Abstract: In this study, 1‐(4‐substitued benzyl)‐3,5‐diphenyl‐1H‐1,2,4‐triazoles (2 a‐e) and ethyl(3,5‐diphenyl‐1H‐1,2,4‐triazole‐1‐yl)acetate (3) were synthesized starting from 3,5‐diphenyl‐1H‐1,2,4‐triazole (1). The ethyl acetate derivative (3) was converted to 2‐(3,5‐diphenyl‐1H‐1,2,4‐triazole‐1‐yl)acetohydrazide (4) in ethanolic medium with hydrazine hydrate. The reaction of the acetohydrazide (4) with suitable isothiocyanates generate 2‐[(3, 5‐diphenyl‐1H‐1,2,4‐triazole‐1‐yl)acetyl]‐4‐methyl/phenyhlthiosemicarbazid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The Schiff base chosen is novel, easy to synthesize, highly aromatic and incorporates phenyl, benzyl, a meta-substituted aryl ring, and 1,2,4-triazole, which provide all the necessary elements for a good photostabilizer. Heterocycles containing the 1,2,4-triazole moiety have various biological activities [18][19][20][21]. The Schiff base enhances the photostability of PS against photodegradation that is a continuation of previously reported work in the area of polymers [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 55%
“…The Schiff base chosen is novel, easy to synthesize, highly aromatic and incorporates phenyl, benzyl, a meta-substituted aryl ring, and 1,2,4-triazole, which provide all the necessary elements for a good photostabilizer. Heterocycles containing the 1,2,4-triazole moiety have various biological activities [18][19][20][21]. The Schiff base enhances the photostability of PS against photodegradation that is a continuation of previously reported work in the area of polymers [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 55%
“…[58] Notably, the nucleoside compounds with a rigid triple bond, whether they have cyclic sugar or not, exhibited highly potent antiviral activity comparable or even more effective than the reference drugs. For example, compounds bearing arylethynyltriazolyl as nucleobase entities (34)(35)(36) act as hit and potent lead antiviral candidates that have been subjected to several structural modifications ( Figure 10). [59] Chudinov and co-workers focused on the structure-activity relationship of 5-arylvinyl analogs with substituents at the 5th position of the triazole ring and the antiviral activity.…”
Section: Ribavirinmentioning
confidence: 99%
“…[34] Moreover, 1,2,4-triazole nucleus displays stability towards each chemical as well as metabolic degradation and can be able to enhance the solubility of the ligand, besides it can substantially improve pharmacokinetics (absorption, distribution, metabolism, and excretion) along with pharmacodynamic properties of the drug because of its polar nature. [35,36] Ribavirin (16) and its analogs, Levovirin (17), and Viramidine (18) are antiviral drugs containing 1,2,4-triazole scaffolds (Figure 4). Ribavirin (Virazole, 1-β-D-ribofuranosyl-1,2,4-triazole-3carboxamide) is a unique antiviral nucleoside agent with a broad antiviral spectrum used against both RNA and DNA viruses, involving influenza A and B types [37] as well as poxviruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the literature data shows that the intensity of research in this area is likely to increase, revealing new useful properties, expanding the existing wide range of biological effects of 1,2,4‐triazole derivatives. Recent studies have found that new representatives of this series revealed antimicrobial, antibacterial,– anti‐fungal, anticonvulsant,– antitumor,– antioxidant, activities, specific activity against influenza A/H1 N1, growth‐stimulating, herbicidal, insecticidal, anti‐tuberculosis, anticholinesterase activities. They inhibit the interaction of annexin A2 and protein S100 A10, HIV 1 replication, p38 MAР kinase, HDAC‐tabulin,– adenosine receptor antagonists, agents in the treatment of Alzheimer's disease, ion channel modulators, etc.…”
Section: Introductionmentioning
confidence: 99%